2019
DOI: 10.1111/lam.13108
|View full text |Cite
|
Sign up to set email alerts
|

Development of real-time loop-mediated isothermal amplification (RealAmp) method for sensitive and rapid detection of pathogenic and nonpathogenicLeptospira

Abstract: Leptospirosis is a zoonotic disease that is spread through water contaminated with the spirochete Leptospira. In our study, RealAmp (real‐time loop‐mediated isothermal amplification) was developed to distinguish between pathogenic and nonpathogenic Leptospira spp. Melt curve analysis of RealAmp showed two distinct melt curves for pathogenic and nonpathogenic Leptospira spp with a Tm value of 90 ± 2 and 88 ± 2°C. The sensitivity of the developed method is as low as 1 pg μl−1 of Leptospira DNA. Specificity was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…This simplicity and low cost enhance its applicability for on‐field screening of pathogens and for limited resourced laboratories (Monica et al . 2019). Regarding its use as a diagnostic tool for animal leptospirosis, it has been successfully applied for detecting leptospiral DNA on cattle and buffalo (Suwancharoen et al .…”
Section: Resultsmentioning
confidence: 99%
“…This simplicity and low cost enhance its applicability for on‐field screening of pathogens and for limited resourced laboratories (Monica et al . 2019). Regarding its use as a diagnostic tool for animal leptospirosis, it has been successfully applied for detecting leptospiral DNA on cattle and buffalo (Suwancharoen et al .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a real-time turbidimeter and colorimetric indicator were used to inspect the LAMP products. The positive curve monitored under a Loopamp real-time turbidimer can be seen directly through the screen during the real-time LAMP (Monica, Rathinasabapathi & Ramya, 2019; Liu et al, 2012). Furthermore, the presence of loop primers can increase the efficiency of amplification and make the detection more rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…The biological samples used in most of these studies were blood or its fractions (serum or plasma) (Ahmed et al, 2014;Denipitiya et al, 2016;Gokmen et al, 2016;Nhan et al, 2014;Waggoner et al, 2015) and urine (Esteves et al, 2018;Podgorsek et al, 2020;Suwancharoen et al, 2016). Rathinasabapathi, & Ramya, 2019;Nhan et al, 2014;Suwancharoen et al, 2016;Waggoner et al, 2015).…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…As an alternative to the high cost of implementing real-time PCR in the routine, the RPA technique (Ahmed et al, 2014) proved to be accurate, with sensitivity and specificity of 94.7% and 97.7%, respectively. The 16SrRNA-PCR-RFLP (Gokmen et al, 2016) and RealAmp (Monica et al, 2019) techniques showed promising results, with an early and accurate diagnosis, which distinguished pathogenic and nonpathogenic species from Leptospira spp. Moreover, a novel multiplex PCR assay has been developed for identifying Orientia tsutsugamushi, Rickettsia typhi and Leptospira spp., causative agents of scrub typhus, murine typhus, and leptospirosis (Sea-Liang et al, 2019).…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%